MAP7D2 Localizes to the Proximal Axon and Locally Promotes Kinesin-1-Mediated Cargo Transport into the Axon - Xingxiu Pan (Cell Reports, 2019)
Summary: The motor protein kinesin-1 plays an important role in polarized sorting of transport vesicles to the axon. However, the mechanism by which the axonal entry of kinesin-1-dependent cargo transport is regulated remains unclear. Microtubule-associated protein MAP7 (ensconsin in Drosophila) is an essential kinesin-1 cofactor and promotes kinesin-1 recruitment to microtubules. Here, we found that MAP7 family member MAP7D2 concentrates at the proximal axon, where it overlaps with the axon initial segment and interacts with kinesin-1. Depletion of MAP7D2 results in reduced axonal cargo entry and defects in axon development and neuronal migration. We propose a model in which MAP7D2 in the proximal axon locally promotes kinesin-1-mediated cargo entry into the axon. : Kinesin-1 is well known for transporting vesicles and organelles into to the axon. Pan et al. show that MAP7D2 concentrates at the proximal axon, regulates kinesin-1 activity, and locally promotes kinesin-1-mediated cargo trafficking into axons. Specific microtubule-associated proteins (MAPs) that locally control motor activities is an emerging concept. Keywords: microtubule, microtubule-associated protein, kinesin, axon initial segment, transport